Lactiplantibacillus plantarum inhibited the growth of primary liver cancer by inducing early apoptosis and senescence, in vitro - Duduyemi, Oladimeji Paul; Potapenko, Kateryna; Limanska, Nataliia; Kotsyuda, Sofiya; Petriv, Nataliia; Suo, Huizhen; Gudzenko, Tetyana; Ivanytsia, Volodymyr; Yevsa, Tetyana (Frontiers in Microbiology, 2024)
Primary liver cancer (PLC), comprising hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), is a severe form of cancer associated with a high mortality and morbidity rate and increasing incidence worldwide. Current treatment options are limited and chemotherapeutics demonstrate strong side effects. New therapies are highly required. Lactobacilli represent the most diverse lactic acid-producing bacteria group and a prominent example of probiotics. Several studies have highlighted the anticancer efficacy of probiotics, especially of Lactiplantibacillus plantarum. However, there are limited studies on its activity on two PLC types, hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). This study evaluated the inhibitory mechanism and properties of L. plantarum ONU 12 (Lp 12) and L. plantarum ONU 355 (Lp 355), isolated from grapes in Ukraine and France, in murine PLC cell lines, in vitro. Strain Lacticaseibacillus casei ATCC 393 (Lc 393) has been taken for a direct comparison, as the most studied probiotic strain. The three Lactobacillus species were used in three forms: as live and heat-killed suspensions, and as sonicated extracts, and tested either as a monotherapy or in combination with standard chemotherapeutics (sorafenib for HCC and gemcitabine for CCA). Cell proliferation and viability were assessed via crystal violet staining assay and cell counting kit-8 assay. The induction of senescence was investigated by senescence-associated β-galactosidase assay. Fluorescence-activated cell sorting analysis was used to determine the apoptotic mechanism behind the inhibitory property of lactobacilli. The results showed that the live suspensions and sonicated extracts of Lp 12, Lp 355, and Lc 393 demonstrated inhibitory properties in CCA and HCC cells after 48 h of incubation. In combinations with standard chemotherapeutics, lactobacilli treatments have shown strong synergistic effects. The combination therapy allowed to reduce the chemotherapeutic doses of gemcitabine from 50 µM to 0.1 and 0.05 µM and sorafenib from 13.8 µM to 6.9 and 3.45 µM. Successful treatment regimes induced early apoptosis and cellular senescence in PLC, as the mechanism of inhibition. Heat-killed suspensions showed no inhibitory effect in none of the cell lines. Both strains, Lp 12 and Lp 355, showed successful results and need further testing in vivo, using autochthonous HCC and CCA models.